microRNA-27a rs895819 is associated with obesity in HIV infected preeclamptic Black South African women on HAART - Maharaj, Niren Ray (BMC Med Genet, 2016)
BACKGROUND: Preeclampsia (PE) and HIV/AIDS present a major health challenge globally. South Africa has the highest disease burden of both HIV/AIDS and PE in the world. Despite extensive research, the pathophysiology of these conditions is not completely understood, however a genetic predisposition in women may affect susceptibility. MiRNA-27a regulates adipogenesis and glucose metabolism. A single nucleotide polymorphism (SNP) in miRNA-27a (rs895819T > C) has shown to have disparate effects in various populations. This study investigated the frequency of rs895819 in pregnant normotensive and preeclamptic Black South African (SA) women. METHODS: Enrollment into the study included: normotensive (n = 95; 45 HIV+; 80 analysed for rs895819T > C, age range: 16–46 years) and PE patients (n = 98; 45 HIV+; 56 analysed for rs895819T > C), age range: 16–42 years). DNA was isolated from peripheral blood mononuclear cells (PBMC). Genotyping of miRNA-27a rs895819 was detected using a TaqMan® SNP Genotyping assay. RESULTS: We did not find a significant association of miR-27a polymorphism with PE susceptibility in our data. However, in the subgroup analysis (based in HIV status), the variant genotypes (TC/CC) were associated with higher body mass index (BMI) among PE women (32.57 vs. 29.25, p = 0.064), significantly in the presence of HIV infection (33.47 vs. 27.8, p = 0.005). CONCLUSION: The results of this study suggests that miR-27a rs895819 may not be associated with PE susceptibility; however, the miR-27a TC/CC genotype increases susceptibility to elevated BMI in PE, which may be significantly influenced by co-morbid HIV infection among pregnant women on HAART.